RESEARCH ON LANGUAGE AND LEARNING: IMPLICATIONS FOR LANGUAGE TEACHING - Alcón, Eva (International Journal of English Studies, 2009)
Taking into account severa1 limitations of communicative language teaching (CLT), this paper calls for the need to consider research on language use and learning through communication as a basis for language teaching. It will be argued that a reflective approach towards language teaching and learning might be generated, which is explained in terms of the need to develop a context-sensitive pedagogy and in terms of teachers' and learners' development.